2021
DOI: 10.1038/s41598-020-79350-7
|View full text |Cite
|
Sign up to set email alerts
|

Antagomir-mediated suppression of microRNA-134 reduces kainic acid-induced seizures in immature mice

Abstract: MicroRNAs are short non-coding RNAs that negatively regulate protein levels and perform important roles in establishing and maintaining neuronal network function. Previous studies in adult rodents have detected upregulation of microRNA-134 after prolonged seizures (status epilepticus) and demonstrated that silencing microRNA-134 using antisense oligonucleotides, termed antagomirs, has potent and long-lasting seizure-suppressive effects. Here we investigated whether targeting microRNA-134 can reduce or delay ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 41 publications
(70 reference statements)
1
12
0
2
Order By: Relevance
“…We next investigated whether inhibiting miR-134 could alter key phenotypes in F1 Ube3a m−/p+ mice. Silencing was achieved using a locked nucleic acid (LNA) antimiR targeting miR-134 (Ant-134), 32 ( Figure 2 E). F1 Ube3a m−/p+ mice received a single intracerebroventricular (ICV) injection at P21 of 0.1 nmol Ant-134 or a scrambled control antimiR (Scr), and brains were extracted 24 h later, to coincide with maximal knockdown.…”
Section: Resultsmentioning
confidence: 99%
“…We next investigated whether inhibiting miR-134 could alter key phenotypes in F1 Ube3a m−/p+ mice. Silencing was achieved using a locked nucleic acid (LNA) antimiR targeting miR-134 (Ant-134), 32 ( Figure 2 E). F1 Ube3a m−/p+ mice received a single intracerebroventricular (ICV) injection at P21 of 0.1 nmol Ant-134 or a scrambled control antimiR (Scr), and brains were extracted 24 h later, to coincide with maximal knockdown.…”
Section: Resultsmentioning
confidence: 99%
“…Preclinical studies have shown that i.c.v injection of antagomir targeting miRNA-134 protects against evoked seizures in multiple rodent models of epilepsy, including models of earlier-life seizures and neurodevelopmental disorders (Reschke et al, 2017;Gao et al, 2019;Campbell et al, 2021;Campbell et al, 2022). In the first study here, we found that suppression of miR-134 by antimiR ASOs did not affect seizure duration, severity or temperature threshold for F1.Scn1a(+/-) tm1kea mice.…”
Section: Discussionmentioning
confidence: 53%
“…Ant-134 does not change the frequency of spontaneous seizures and SUDEP in F1.Scn1a(+/-) tm1kea mice Some therapeutics may fail against hyperthermia-induced seizures but nevertheless work against spontaneous seizures and SUDEP (Hawkins et al, 2017). Previous work showed that Ant-134 when injected at 0.1 nmol reduced seizures evoked by systemic kainic acid in P21 mice (Campbell et al, 2021).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Introduction of an miRNA manipulation would need to be performed with full knowledge of potential interactions. Our laboratory has made recent progress in this regard, observing that while the antiseizure effects of Ant-134 are retained in juvenile mice, these animals were less tolerant of higher doses [108]. Beyond this, clinical development will likely require partnering with biotechnology or pharmaceutical companies.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%